(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The consumer choice theory postulates why individuals purchase products. It means that you choose to spend your money on the things that will make you the happiest while staying within your means. The products of GNA Axles Limited are Fully Floating Axles, Fixed Axles, Stub Axles, Semi Floating Axles and Half Axles etc. 80% of trucks & tractors have GNA's axles fitted. GNA make a range for vehicles up to 25 tones capacity. The study encompasses the employees understanding regarding the company’s products in the market and the attribute influencing the sale of the products with reference to GNA Axles Limited, Hoshaipur.